2015
DOI: 10.1111/apha.12552
|View full text |Cite
|
Sign up to set email alerts
|

The influence of light on thermal responses

Abstract: Light is essential for vision and plays an important role in non-visual responses, thus affecting alertness, mood and circadian rhythms. Furthermore, light influences physiological processes, such as thermoregulation, and therefore may be expected to play a role in thermal comfort (TC) as well. A systematic literature search was performed for human studies exploring the relation between ocular light exposure, thermophysiology and TC. Experimental results show that light in the evening can reduce melatonin secr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
54
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(59 citation statements)
references
References 115 publications
2
54
0
3
Order By: Relevance
“…Melatonin might therefore also affect skin temperature locally. Since melatonin affects temperature regulation on multiple levels and changes in body temperature correlate to altered alertness, it has been suggested that melatonin induces sleepiness via influencing body temperature . In our experiment, melatonin administration did not result in a significant decrease in T tongue , although subjective sleepiness increased.…”
Section: Discussionsupporting
confidence: 84%
“…Melatonin might therefore also affect skin temperature locally. Since melatonin affects temperature regulation on multiple levels and changes in body temperature correlate to altered alertness, it has been suggested that melatonin induces sleepiness via influencing body temperature . In our experiment, melatonin administration did not result in a significant decrease in T tongue , although subjective sleepiness increased.…”
Section: Discussionsupporting
confidence: 84%
“…Two studies found a cooler thermal sensation under low light intensity as compared to bright light, while the third experiment reported no significant effect of light intensity on thermal comfort and thermal sensation . Additionally, changes in thermal sensation caused by the intensity of light may be related to changes in core body temperature . In conclusion, it remains unclear why in some studies the light exposure affected thermal sensation, while in others it did not.…”
Section: Introductionmentioning
confidence: 85%
“…This compensation may contribute to a comfortable indoor environment while simultaneously reducing building energy consumption. One theory about the interaction between temperature and light is the hue‐heat hypothesis and states that “an environment which has dominant light frequencies toward the red end of the visible spectrum feels warm and one with dominant blue frequencies feels cool.” Several studies confirm this association between light with short wavelengths and a cool thermal sensation compared to light with long wavelengths . More recently, the study of Huebner et al.…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations